Demokrasi di Pakistan Menurut Benazir Bhutto - Irnawati, Irnawati (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article discusses about democracy in Pakistan by Benazir Bhutto. The realization of democracy in Pakistan, according to Benazir Bhutto, is to reach all the democratic elements of the Pakistani nations, the business communities, to release all of the political prisoners, to make the print and electronic media free, to open and uncensored, to remove the ban on sororities and labor, to separate the judicial functions of the executive, and to provide the basis for a fair electoral process. The other leaderships of women in Pakistanâs democracy by Benazir Bhutto, are appointing some women to sit in the cabinet and set up the Ministry of Women Development, creating the program of study in the universities for women, founding the Women Development Bank to provide credit only for the women entrepreneurs, creating institutions to train women in family planning, nutrition counseling, child care, and birth control. Democracy in Pakistan is a liberal democracy which is characterized by a moderate Islam, by recruiting people who are competent to sit in the government, eliminating and restricting military power, reactivating the role of civil society in accordance with the governmentâs program.Keywords: Democracy, Pakistan, Benazir Bhutto.